The application of dental mesenchymal stem cells (DMSCs) in the repair of oral and maxillofacial defects - Chen, Yiqi; Ma, Xikun; Mai, Huaqing; Lai, Pengyu; Huang, Renlong; Alimujiang, Adili (Frontiers in Bioengineering and Biotechnology, 2025)
Dental mesenchymal stem cells (DMSCs) are important seed cells for oral and maxillofacial tissue regeneration due to their wide availability, multi-directional differentiation potential, strong proliferation ability, maintenance of stemness after multiple proliferations, and immunomodulatory capacity. DMSCs have a wide range of sources, and different subtypes have different properties. They can promote tissue regeneration through direct differentiation into tissue cells, improvement of the local regeneration microenvironment through immunomodulatory functions, and release of various bioactive components. The article reviews the classification of DMSCs, their performance comparisons in recent years, methods of promoting tissue regeneration, and their applications in maxillofacial bone and soft tissue. Furthermore, the review explores DMSCs’ excellent abilities to promote bone tissue repair when supported by various materials and repair maxillofacial soft tissue defects by promoting the regeneration of special structures of teeth such as dentin, cementum, and dental pulp vessels and nerves.